2019
DOI: 10.1002/ep.13358
|View full text |Cite
|
Sign up to set email alerts
|

Binary adsorption of Cu(II) and Ni(II) on Lai'yang bentonite: Kinetics, equilibrium, competition quantitative and mechanisms investigation

Abstract: In this study, the competitive adsorption of Cu(II) and Ni(II) adsorption onto bentonite were investigated. The effects of initial adsorbate concentration, pH, contact time, temperature on adsorption and the kinetics, thermodynamic, quantification of adsorption competition and competitive mechanisms have been studied. The results indicated that Cu(II) has a higher affinity than Ni(II) for adsorption on bentonite. But the inhibition effect was not noticeable under alkaline conditions. The Langmuir and pseudo-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…5, the adsorp- www.nature.com/scientificreports/ tion of heavy metal ions by BC and M-BCs can be divided into two stages: fast stage and slow stage. These results were consistent with the adsorption of heavy metal ions by other biochars [29][30][31][32] . This indicated that in the rapid adsorption stage, the adsorption of heavy metal ions by biochar mainly occurs on the surface of biochar, with physical adsorption predominating.…”
Section: Target Heavy Metal Ions Adsorption Kinetics Of Target Biocha...supporting
confidence: 89%
“…5, the adsorp- www.nature.com/scientificreports/ tion of heavy metal ions by BC and M-BCs can be divided into two stages: fast stage and slow stage. These results were consistent with the adsorption of heavy metal ions by other biochars [29][30][31][32] . This indicated that in the rapid adsorption stage, the adsorption of heavy metal ions by biochar mainly occurs on the surface of biochar, with physical adsorption predominating.…”
Section: Target Heavy Metal Ions Adsorption Kinetics Of Target Biocha...supporting
confidence: 89%
“…Keeping the Cu 2+ constant and increasing the Ni 2+ concentration up to 50 mg/ml still resulted in no uptake of Ni 2+ at all, suggesting a highly specific adsorption of Cu 2+ against Ni 2+ . The known lower first hydrolysis constant, 39 higher Lewis acid hardness, 40 and higher second ionization energy of Cu ion 41 were supposedly to collectively lead to the specificity. The increasing Ni 2+ , however, shielded Cu 2+ in the solution, therefore, the adsorptive capacity of Cu 2+ gradually decreased to 1.06 mmol/g, which had been commonly observed in the literature 7,8 …”
Section: Resultsmentioning
confidence: 99%